2011
DOI: 10.1111/j.1472-4642.2011.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape context affects the success of habitat restoration: large‐scale colonization patterns of saproxylic and fire‐associated species in boreal forests

Abstract: Aim  Restoration of habitats may be used as a conservation tool when ecosystems have lost their natural structure, dynamics or functioning over large areas. Controlled and planned use of fire could be an effective way to restore habitats of many threatened species in boreal forests where fire suppression has been effective. We asked whether the large‐scale landscape context affects the occurrence of rare and threatened species in forest habitats that have been burned to restore their fire‐related structures. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 52 publications
(74 reference statements)
3
65
1
Order By: Relevance
“…These ecosystems are strongly adapted to fire disturbance (Granstrom, 2001;Hylander, 2011;Pereira et al, 2013a, b). However, climate change, recent land-use change and fire suppression policies, may have important implications on the fire regime, fire severity and the role of fire in boreal environments (De Groot et al, 2013;Kouki et al, 2012;Van Bellen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These ecosystems are strongly adapted to fire disturbance (Granstrom, 2001;Hylander, 2011;Pereira et al, 2013a, b). However, climate change, recent land-use change and fire suppression policies, may have important implications on the fire regime, fire severity and the role of fire in boreal environments (De Groot et al, 2013;Kouki et al, 2012;Van Bellen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is not clear and other studies have reported positive effects of fire on red-listed species (Hekkala et al 2014;Kouki et al 2012). However, the inherently low abundance of red-listed species increases the influence of stochasticity in the data and makes it more difficult to identify patterns.…”
Section: Magdalis Violaceamentioning
confidence: 53%
“…However, the inherently low abundance of red-listed species increases the influence of stochasticity in the data and makes it more difficult to identify patterns. Other possible explanations for this lack of response are that intensively forest management in this landscape has resulted in an impoverished regional species pool of red-listed species, as shown in other studies (Kouki et al 2012); alternatively, that rare low density red-listed species should be expected to exhibit a slower response to fire than more abundant early successional saproxylic species. Hekkala et al (2014) reported that both the species richness and abundance of rare and red-listed species was higher the second year after fire compared to the first year after fire.…”
Section: Magdalis Violaceamentioning
confidence: 98%
“…Therefore, it appears that it may be difficult to restore aspen (or any other species) in forests if the ecosystem (and its surrounding matrix) is very far from its natural state. Because the dispersal ability varies greatly depending on the species to be restored (Jonsson et al 2005;Kouki et al 2012;Norros et al 2012), the effect of dispersal constraint is species-specific. Since aspen often regenerates through root suckers, a better result in terms of reaching restoration targets could perhaps be achieved by introducing the species by highly artificial means, for instance by the planting of trees.…”
Section: Main Results and Discussionmentioning
confidence: 99%